The Impact of Chronic Suppurative Otitis Media on Quality of Life in the Elderly - Desi Kamilasari; Agus Zuliyanto; Oke Kadarullah; Yunia Annisa (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2026)
Chronic Suppurative Otitis Media (CSOM) is a chronic ear infection that can cause hearing impairment and negatively affect the quality of life, particularly among elderly individuals. This study aimed to determine the relationship between CSOM and quality of life among the elderly at Wijayakusuma Class III Hospital, Purwokerto. This research used a quantitative analytic design with a cross-sectional approach. A total of 46 elderly respondents diagnosed with CSOM were selected using medical record data. Data were collected using a validated questionnaire consisting of 26 items to measure quality of life. Data analysis was performed using univariate analysis and bivariate analysis with Chi-square and Fisher’s Exact Test. The results showed that most respondents had active CSOM (71.7%), and the majority experienced poor quality of life (93.5%). Statistical analysis using Fisher’s Exact Test showed a significant relationship between CSOM type and quality of life among the elderly (p = 0.019). In conclusion, CSOM is significantly associated with decreased quality of life in elderly patients. These findings highlight the importance of early detection, proper treatment, and comprehensive management of CSOM to improve the quality of life of elderly patients.